2015
DOI: 10.9738/intsurg-d-14-00135.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anterior Versus Posterior Approach in the Treatment of Thoracolumbar Fractures: A Systematic Review

Abstract: Despite extensive research on thoracolumbar fractures, controversy still exists about which approach is the most appropriate. Lack of evidence-based practice may result in patients being treated inappropriately. The objective of study was to perform a systematic review of the effectiveness of the anterior and posterior approaches in the treatment of thoracolumbar fractures. We conducted searches of PubMed and the Cochrane Library, searching for relevant trials up to August 2013 that compared anterior and poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
1
26
0
10
Order By: Relevance
“…The surgeon has to determine the best approach (i.e., anterior-only, posterior-only, or combined anterior-posterior), each with their relative advantages and disadvantages. A comparison between isolated anterior and posterior approaches has been the focus of previous systematic reviews and are outside the scope of this study [10,11]. These reviews have largely found no differences in terms of the neurological, functional, and quality-of-life outcomes between the anterior-only and the posterior-only approaches.…”
Section: Discussionmentioning
confidence: 98%
“…The surgeon has to determine the best approach (i.e., anterior-only, posterior-only, or combined anterior-posterior), each with their relative advantages and disadvantages. A comparison between isolated anterior and posterior approaches has been the focus of previous systematic reviews and are outside the scope of this study [10,11]. These reviews have largely found no differences in terms of the neurological, functional, and quality-of-life outcomes between the anterior-only and the posterior-only approaches.…”
Section: Discussionmentioning
confidence: 98%
“…fractures that focuses specifically on true burst fractures only. Previous review articles have included fractures of differing morphologies and pathologies(21,22). The present review, by focusing on burst fractures only, improves the generalizability of the recommendations made.A comprehensive evaluation of treatment outcomes is made possible by both qualitative and quantitative meta-analysis of the results.…”
mentioning
confidence: 91%
“…2,19,23 Anterior, posterior, and combined approaches have been described, although posterior approaches present potentially less complications. 2,19,23 We did not find any recent study proposing nonoperative management for burst fractures in neurologically-compromised patients. With few exceptions, a mild radiculopathy (N2) associated with a burst fracture may be treated nonoperatively.…”
Section: Types A3-a4 (Incomplete and Complete Burst Fractures)mentioning
confidence: 99%